Association patterns between plant cover and soil quality of the coastal dune scrubland in Ria Lagartos Reserve, Yucatan - Leirana-Alcocer, Jorge Leandro (Universidad Autónoma de Tamaulipas, 2014)
Restoration actions in the Ria Lagartos Reserve includes planting native species; however, the relation between ecosystem properties and these species in their natural habitats has not been documented. This work describes the relation between the cover plant of the three dominant shrub species and some soil properties in the coastal dune scrubland. Thirty quadrats of 4 m2 were sampled. The cover percentage of every species was recorded, as well as the litter cover on soil (LC). Soil samples were taken at each quadrat, measuring PH, electric conductivity (EC), apparent density (AD), total nitrogen content (TN), organic matter percentage (OM) and gray tone (GT). Correlation analyses were performed between those variables and the cover of the three dominant shrub species: Pithecellobium keyense, Bumelia retusa and Enriquebeltrania crenatifolia. P. keyense and B. retusa were correlated to LC; P. keyense was also correlated to OM and had a tendency to increase with N; E. crenatifolia was correlated to EC. In addition, it was observed that GT correlated with most all of the variables except with pH and LC; and that TN and AD were correlated with most all of the edaphic variables except with pH and CE. Results suggest that P. keyense could be a soil improvement species and that DA and TG are easy to measure and inexpensive proxies to evaluate soil quality in this site.